IL6 Induces mtDNA Leakage to Affect the Immune Escape of Endometrial Carcinoma via cGAS-STING - Xue Zeng; Xiaosong Li; Yundong Zhang; Chaoxia Cao; Qin Zhou (Journal of Immunology Research)
Endometrial carcinoma (EC) is a commonly diagnosed gynecological malignancy. Interleukin-6 (IL6) plays a critical role in modulating the progression of several types of tumors, including EC. However, the specific mechanism of IL6 in regulating EC progression has not been clearly elucidated. In this study, we performed a series of functional experiments to explore the potential mechanisms involved in IL6 function in the progression of EC. Here, we found that IL6 increased reactive oxygen species (ROS) generation by enhancing the NADPH oxidase (NOX) level and induced mtDNA leakage in EC cells, which further caused the activation of the downstream cGAS-STING signaling and increased production of extracellular vesicle (EV) production from EC cells. Besides, the activation of cGAS-STING signaling enhanced the expression of type I IFN and its downstream molecule PD-L1 through the TBK1-IRF3 pathway. Importantly, a high level mtDNA and PD-L1 were present in EVs derived from IL6-induced EC cells; these vesicles were shown to be able to induce T cell apoptosis. Finally, anti-PD-L1 treatment in mice showed that blockade of PD-L1 significantly reversed tumor immune escape mediated by IL6-induced EVs. Together, we provide evidence that IL6 induced mtDNA leakage to regulate the immune escape of EC cells. Our findings may provide a novel clue for the development of therapeutic targets for EC.